2019
DOI: 10.1042/bsr20181596
|View full text |Cite
|
Sign up to set email alerts
|

Cell migration on microposts with surface coating and confinement

Abstract: Understanding cell migration in a 3D microenvironment is essential as most cells encounter complex 3D extracellular matrix (ECM) in vivo. Although interactions between cells and ECM have been studied previously on 2D surfaces, cell migration studies in 3D environment are still limited. To investigate cell migration under various degrees of confinements and coating conditions, 3D platforms with micropost arrays and controlled fibronectin (FN) protein coating were developed. MC3T3-E1 cells spread and contacted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Topographical guiding patterns. Osteoblast cell migration has been the primary focus of many topographical guiding effect studies 13,[23][24][25] . In this paper, three aspects of surface topography were used to investigate the impact of different guiding patterns on MC3T3-E1 osteoblast cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…Topographical guiding patterns. Osteoblast cell migration has been the primary focus of many topographical guiding effect studies 13,[23][24][25] . In this paper, three aspects of surface topography were used to investigate the impact of different guiding patterns on MC3T3-E1 osteoblast cell migration.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, NP460 cells migrated with better alignment to the grating orientation of the top layer on platforms that were fully coated with FN. It is suggested that the NP460 cells became more sensitive to the topographical changes on the platforms with FN coating, perhaps related to the improved cell-surface interaction by enhancing the biocompatibility and hydrophilicity of the PDMS substrate [54]. Taken together, this study demonstrates that this two-layer scaffold platform can be used to access the changes in EMT on cell invasiveness that is otherwise only detectable by the use of specific biomarkers.…”
Section: Fibronectin Coating Enhanced Traversing Behavior Of Tgf-β1-tmentioning
confidence: 74%
“…Similarly, cells encounter complex microenvironments during 3D cell migration. Cells were studied on microposts with different surface coatings and post spacings to mimic physical confinement . Cells traveled faster on the tops of microposts, while cells squeezing between microposts were slower.…”
Section: Deformable Structuresmentioning
confidence: 99%
“…To further investigate how cells respond to a confined space, they were covered with a second set of microposts. When the spacing between the top and bottom microposts was reduced such that cells could adhere to both sets of microposts, it was found that they migrated at a higher speed . In another study, cell migration toward a chemotactic stimulus was observed inside a microfluidic device consisting of microposts embedded in channels of varying cross‐sectional area .…”
Section: Deformable Structuresmentioning
confidence: 99%